HOTEL MANAGEMENT STRATEGY : A CASE STUDY OF SMALL HOTELS IN MUANG DISTRICT, CHIANG RAI PROVINCE - Phannipha Saokham, พรรณิภา ซาวคำ (Dusit Thani College Journal, 2018)
The purposes of this research were 1) to study the management of small hotels in Muang District, Chiang Rai and 2) to present the strategy for small hotels management in Muang District, Chiang Rai. The qualitative method was used in this research. The data was collected from in-depth interviews with the owner, manager and employees of a small hotel, which means not more than 30 rooms, for studying the management of small hotels in Muang District, Chiang Rai and purposive sampling with 3 small hotels being Rasa Boutique Hotel Chiang Rai, Amarin Resort Chiang Rai and Mohn Fah Sai Home Resort to present the strategy for small hotel management in Muang District, Chiang Rai. The results of this study were (1) Planning, most of the hotels focus on service, revenue management and the hotel’s stunning decoration (2) Management, most of hotel staff received verbal orders directly from owners or managers and no document or memo (3) Direction, most of the hotels divide the organization according to responsibilities with simple divisions in each department (4) Coordination, most of the hotels used oral communication between departments (5) Controlling, most of the hotels made outlines for duties to control staff to be standardized. The small hotel management strategies comprise of 4 strategies: (1) Approach Strategy, to develop appropriately management resources (4M) (2) Development Strategy, management is carried out in a participatory manner in the organization (3) Defensive Strategy, to develop the marketing potential of a small hotel (4) Flexible Strategy, to develop the small hotel to accommodate specific niche tourism sectors.